Bug off or bug out: mapping flight secrets of Triatoma garciabesi (Hemiptera: Reduviidae) through climate, geography, and greenery - Verly, Thaiane; Fiad, Federico G.; Carbajal-de-la-Fuente, Ana Laura; Pita, Sebastián; Piccinali, Romina V.; Lobbia, Patricia A.; Sánchez-Casaccia, Paz; Rojas de Arias, Antonieta; Cavallo, María José; Gigena, Gisel V.; Rodríguez, Claudia S.; Vega-Gómez, María C.; et al. (Frontiers in Insect Science, 2025)
IntroductionTriatoma garciabesi is a vector of Trypanosoma cruzi, the causative agent of Chagas disease, and is found across northwest and central Argentina, southern Bolivia, and western Paraguay. It frequently invades rural houses during the warm seasons and is common in peridomestic and wild environments. Recently, the existence of two lineages has been demonstrated based on variation in cytochrome c oxidase I gene (coI). These lineages occur across the species distribution range and coincide with different ecological regions. Here, we aim to examine how phenotypic variation in flight-related traits is structured, determine the association between these traits and geographic distance, and identify the climatic, geographic, and/or vegetation cover variables that best explain the morphometric variation in flight-related traits.MethodsA total of 198 males of T. garciabesi from 24 populations in Argentina and Paraguay were included in this study, covering almost the entire T. garciabesi distribution range. Size and shape components of the forewing, membranous, and stiff portions of the forewing and head were measured using a landmark-based methodology.ResultsOur study documents that the size component of the membranous and stiff portions showed significant variation across the species range. Although forewing and head shape did not show significant differences in Procrustes distances across all pairs of populations, the membranous and stiff portions did. There is a strong and consistent association between shape and geographic distances at all levels of comparison (species and lineage ranges). The size and shape components and the geographic, climatic, and/or vegetation indexes explained covariation in all flight-related traits.DiscussionT. garciabesi appears to be a species sensitive to vegetation cover and landscape features. This study provides evidence for this by showing clear variation in flight-related traits across the species and lineage distribution range, as well as indications of isolation by distance and variation in flight-related traits according to climate, geography, and vegetation cover.